THE COMPARISON BETWEEN METAPHORS USED IN POLITICAL NEWS IN THE JAKARTA POST AND THE NEW YORK TIMES ONLINE - Riskia Sitti Velini; Hermawati Syarif (Universitas Negeri Padang, 2019)
This study analyzed the differences and the similarities between metaphors found in political news in The Jakarta Post and The New York Times online. Kovecses (2010) theory about conceptual metaphor is used to analyze the data. The concept of metaphor is elaborated into source domain and target domain. The type of this research is qualitative descriptive. After analyzing 40 political news in The Jakarta Post and The New York Times, it was found that there are 61 metaphors in the The New York Times and 16 metaphors in The Jakarta Post. The result of this study shows that politics is the most dominant type of target domain in the metaphors found in both newspapers. However, the most dominant type of source domain is different. In The New York Times, it is found that the most dominant type of source domain is movement and direction. Meanwhile in The Jakarta Post, the most dominant type of source domain is machines and tools. The differences occur because the writers of both NYT and TJP have different cultural background and writing style.